Mesophase pitch carbon matrix modified high-thermal-conductivity C / SiC composite material and preparation method thereof
Through the mesophase asphalt carbon matrix modification process, the problems of low thermal conductivity and limited use temperature of C/SiC composites are solved, and the preparation of C/SiC composites with high thermal conductivity and excellent mechanical properties are achieved, simplifying the process and reducing costs.
Patent Information
- Application Number
- CN202510030522.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-03-18
AI Technical Summary
The existing C/SiC composite materials have low thermal conductivity, limited use temperature, and the high thermal conductivity matrix improvement process is complex and costly.
The mesophase asphalt carbon matrix modification process is used to obtain high thermal conductivity C/SiC composite materials through phenolic resin solution impregnation, infrared lamp or oven drying, hot-molded pressurized curing, and carbonization treatment.
The thermal conductivity and mechanical properties of the composite material are significantly improved, and the bending strength and thermal conductivity reach 176.31MPa-220.89MPa and 124.15W/(m·K)-288.22W/(m·K), respectively, and the preparation process is simplified, the preparation cycle is shortened, and the cost is reduced.
Smart Images

Figure CN119638467A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of high thermal conductivity C / SiC composite materials, and specifically relates to a mesophase pitch carbon matrix modified high thermal conductivity C / SiC composite material and a preparation method thereof. Background Art
[0002] With the continuous development of modern science and technology, the flight speed of hypersonic aircraft is constantly increasing. During high-speed flight, due to aerodynamic heating, the temperature of its outer surface rises sharply, especially at the leading edge, end and other tip parts. Hypersonic aircraft need to fly in an aerobic and high-temperature environment for tens to thousands of seconds, and their service time in an oxidizing and high-temperature environment is relatively long. Under such a long period of aerodynamic heating, the surface temperature of the hot end parts such as the end and leading edge of the aircraft will exceed 2000℃.
[0003] At present, the main high-temperature structural material used to prepare the leading edge is C / SiC composite material made of polyacrylonitrile (PAN)-based carbon fiber such as T300 and T700 series carbon fiber. It has the advantages of high high-temperature structural strength and good oxidation resistance and ablation resistance, but its long-term use temperature generally does not exceed 1650℃, and short-term use temperature does not exceed 1800℃. At the same time, its thermal conductivity is low and heat cannot be transferred in time, resulting in high stagnation temperature of the leading edge. It is easy to cause the leading edge and other parts to have large thermal temperature differences, resulting in thermal stress concentration, serious structural deformation, and affecting other functions of the aircraft. These shortcomings seriously limit its application in parts such as the end and leading edge of the aircraft where the use temperature exceeds 2000℃.
[0004] The thermal conductivity of the graphitized mesophase pitch carbon fiber can reach 800W / (m·K)~1000W / (m·K). Replacing the commonly used PAN-based fibers with it can effectively improve the thermal conductivity of the composite material. However, since the SiC matrix prepared by the PIP process contains a certain porosity, the pores in the matrix become the resistance to heat conduction. Therefore, the thermal conductivity of the composite material prepared by only using mesophase pitch carbon fiber is limited.
[0005] In summary, the matrix needs to be further modified to further improve the thermal conductivity of the composite material. Summary of the invention
[0006] In view of the problem that most commonly used thermal conductive carbon matrices in the prior art adopt chemical vapor deposition process, which has a long preparation cycle, high cost, and requires complex process equipment, the present invention provides a mesophase pitch carbon matrix modified high thermal conductive C / SiC composite material and a preparation method thereof. The present invention aims to solve the problems of low thermal conductivity, limited use temperature, complex and high cost of high thermal conductive matrix improvement process of existing C / SiC composite materials, and provide a simple and rapid method for preparing high thermal conductive C / SiC composite materials.
[0007] The purpose of the present invention is achieved through the following technical solutions: A method for preparing a mesophase pitch carbon matrix modified high thermal conductivity C / SiC composite material comprises the following steps: S1. Fiber preform shaping treatment: The fiber preform is placed under vacuum conditions, impregnated with phenolic resin solution, and then dried in an infrared lamp or a 60°C oven. It is heated to the softening temperature of phenolic resin in a hot molding device and then pressurized. The temperature is then raised to the phenolic resin curing temperature and the heat and pressure are maintained. Finally, the cured sample is carbonized in a high-temperature furnace to obtain a carbon fiber skeleton with a fiber volume fraction of 35% to 55%. The solvent of the phenolic resin solution is anhydrous ethanol, the mass fraction of the phenolic resin is 10% to 30%, the phenolic vacuum impregnation time is 4h to 8h, the drying time is 6h to 8h, the phenolic softening temperature is 90°C to 110°C, the pressure during softening is 1MPa to 5MPa, the holding time is 1h to 3h, the curing temperature is 180°C to 200°C, the curing holding time is 1 to 2h; the carbonization temperature is 800°C to 1000°C, the holding time is 1h to 3h, and the carbonization heating rate is 5°C / min to 10°C / min; The fiber preform is a 2D stitched mesophase asphalt carbon fiber preform or a three-dimensional fine-woven puncture structure mesophase asphalt carbon fiber preform, wherein the mesophase asphalt carbon fiber is a fiber that has not been graphitized; the carbon fiber cloth used for the 2D stitched preform is a satin or twill mesophase asphalt carbon fiber cloth, and the stitching spacing is 3mm / needle to 6mm / needle; the puncture needle spacing of the three-dimensional fine-woven puncture structure carbon fiber preform is 2mm / needle to 4mm / needle; the 2D stitched preform, the stitching fiber and the three-dimensional fine-woven puncture structure carbon fiber are T300, T700, T800, M40J and other polyacrylonitrile-based carbon fibers; S2. Preparation of mesophase pitch carbon matrix: using a pyrolysis furnace to achieve melt impregnation of mesophase impregnated pitch, in-situ mesophase conversion of pitch and in-situ carbonization to obtain a mesophase pitch carbon matrix, specifically comprising the following steps: S2-1, placing the carbon fiber skeleton obtained in S1 in a shaped crucible with the inner surface of the inner surface coated with a release agent and the same outer dimensions as the carbon fiber skeleton, leaving a positive tolerance margin of 0.5 mm around the crucible, and padding the bottom of the crucible with a 0.5 mm graphite strip to support the carbon fiber skeleton, calculating the mass of the mesophase asphalt required for impregnation according to the porosity of the carbon fiber skeleton after shaping in S1, weighing the mesophase asphalt powder for impregnation containing the required weight of 10% to 15% of the surplus, and spreading it flat on the carbon fiber skeleton, and placing the crucible in a cracking furnace; S2-2, after the cracking furnace is evacuated, the vacuum state is maintained, and the temperature is raised to the melting point of the mesophase pitch at a rate of 5°C / min and kept warm, so that the molten pitch is impregnated into the carbon fiber skeleton through the pores; S2-3, after the impregnation is completed, inert gas argon or nitrogen is introduced into the furnace, and the temperature is continued to be raised to the asphalt mesophase transformation temperature, and the temperature is maintained until the asphalt mesophase transformation is completed; S2-4, finally continue to raise the temperature to the pitch carbonization temperature to obtain a carbon skeleton modified with a primary mesophase pitch carbon matrix; The carbon yield of the mesophase pitch for impregnation is 45-55wt%; the heating rate of the pitch melting, mesophase conversion and carbonization process is 5°C / min, the melting point of the pitch is 90°C-110°C, the insulation time during melting is 3h-5h, the mesophase conversion temperature is 380°C-400°C, the insulation time is 7h-10h, the carbonization temperature is 900°C-1000°C, the insulation time is 1h-3h; S3, repeating the mesophase pitch melt impregnation, in-situ mesophase conversion, and in-situ carbonization process in S2 0 to 4 times to obtain a carbon skeleton containing 1 to 4 times of pitch carbon matrix modification; S4, graphitization treatment: the carbon skeleton modified by the asphalt carbon matrix obtained in S3 is placed in a graphitization furnace for high-temperature treatment, the graphitization temperature is 2800℃~3200℃; the heat preservation time is 1h~3h. During the graphitization treatment, the mesophase asphalt carbon fiber and the mesophase asphalt carbon matrix introduced in S2 and S3 are graphitized, and the thermal conductivity of the mesophase asphalt carbon fiber and the mesophase asphalt carbon matrix is stimulated; S5. Preparation of silicon carbide matrix: using the process in S2 to perform solid polycarbosilane melt impregnation and in-situ cracking: The graphitized carbon skeleton containing mesophase pitch carbon modification in S4 is placed in a contoured crucible coated with a release agent, and a 0.5 mm graphite strip is placed on the bottom of the crucible to support the carbon skeleton. The mass of solid polycarbosilane required for impregnation is calculated according to the porosity of the carbon skeleton in S4, and solid polycarbosilane powder containing 10% to 15% of the required weight of the residual is weighed on the carbon skeleton containing mesophase pitch carbon modification, and the crucible is placed in a cracking furnace; After the cracking furnace is evacuated, the vacuum state is maintained, and the temperature is raised to the melting point of polycarbosilane at a rate of 5°C / min, and the temperature is kept for 4h to 5h, so that the molten polycarbosilane is impregnated into the sample through the capillaries. After the impregnation is completed, an inert gas argon or nitrogen is introduced into the furnace, and the temperature is continued to be raised to 1000°C to 1300°C at a rate of 5°C / min, and the temperature is kept for 1h to 3h to crack the polycarbosilane into a silicon carbide matrix; The melting point of the polycarbosilane used for impregnation is 190°C to 220°C, and the ceramic yield is about 50wt%; S6, repeating the polycarbosilane melt impregnation and in-situ cracking process in S5 for 6 to 10 times to complete the densification of the composite material to obtain a mesophase pitch carbon matrix modified high thermal conductivity C / SiC composite material; The prepared mesophase pitch carbon matrix modified high thermal conductivity C / SiC composite material has excellent mechanical and high thermal conductivity properties, with a flexural strength of 176.31MPa-220.89MPa and a thermal conductivity of 124.15W / (m·K)-288.22W / (m·K).
[0008] The present invention also relates to a mesophase asphalt carbon matrix modified high thermal conductivity C / SiC composite material, which is obtained by the preparation method of the above-mentioned mesophase asphalt carbon matrix modified high thermal conductivity C / SiC composite material. The composite material has excellent mechanical and high thermal conductivity properties, a bending strength of 176.31MPa-220.89MPa, and a thermal conductivity of 124.15W / (m·K)-288.22W / (m·K).
[0009] Compared with the prior art, the present invention has the following advantages: 1. The method for preparing a mesophase asphalt carbon matrix modified high thermal conductivity C / SiC composite material described in the present invention comprises the following steps: modifying the high thermal conductivity matrix by mesophase asphalt melt impregnation, in-situ mesophase conversion, and in-situ carbonization; combining mesophase asphalt carbon fibers as reinforcements; and densifying the silicon carbide matrix by polycarbosilane melt impregnation and in-situ cracking processes. The obtained mesophase asphalt carbon matrix modified high thermal conductivity C / SiC composite material has excellent mechanical and high thermal conductivity properties, can be widely used in the leading edge, end, and other parts of hypersonic aircraft, and can effectively improve the material use temperature and service environment.
[0010] 2. The method for preparing a mesophase asphalt carbon matrix modified high thermal conductivity C / SiC composite material described in the present invention adopts an mesophase asphalt carbon matrix to replace the complex chemical vapor deposition (CVI) carbon matrix to modify the thermal conductivity of the composite material. The mesophase asphalt carbon matrix has a clear orientation along the fiber axis during the graphitization process, which can greatly improve the in-plane thermal conductivity of the composite material. On the basis of achieving improved thermal conductivity, the preparation process can be simplified, the preparation cycle can be shortened, and the manufacturing cost can be saved. At the same time, unlike the previous liquid phase process for preparing composite materials, the impregnation equipment, drying and curing equipment, and cracking and carbonization equipment are used separately. In the cracking furnace, the impregnation, in-situ carbonization or cracking of the precursor are achieved at one time through the contoured design of the crucible, which not only saves raw materials, but also greatly simplifies the process and process equipment, and shortens the material preparation cycle.
[0011] 3. The method for preparing a mesophase asphalt carbon matrix modified high thermal conductivity C / SiC composite material described in the present invention successfully prepared a modified C / SiC composite material with excellent mechanical properties and high thermal conductivity. Compared with the prior art, the preparation method of the present invention has the advantages of simple operation, low cost and high efficiency. The material preparation cycle can be shortened to 10 to 15 days. This method provides a new approach for the preparation of high thermal conductivity C / SiC composite materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention.
[0013] Figure 1 This is a process flow chart of a method for preparing a mesophase pitch carbon matrix modified high thermal conductivity C / SiC composite material according to the present invention; Figure 2 This is a scanning electron microscope photograph of the mesophase pitch carbon matrix modified high thermal conductivity C / SiC composite material prepared in Example 1 of the present invention; Figure 3 This is a scanning electron microscope photograph of the mesophase pitch carbon matrix modified high thermal conductivity C / SiC composite material prepared in Example 3 of the present invention. DETAILED DESCRIPTION
[0014] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0015] Embodiment 1: A method for preparing a mesophase pitch carbon matrix modified high thermal conductivity C / SiC composite material comprises the following steps: The mesophase asphalt carbon fiber preform was stitched with 2D satin cloth stitched with T300 carbon fiber as stitching thread at a stitch length of 3mm / needle, placed under vacuum conditions, immersed in a 10% phenolic resin ethanol solution for 6 hours, dried under an infrared lamp for 8 hours, and then heated to 110°C in a hot molding device and pressurized at a pressure of 3MPa. After holding the pressure for 1 hour, the temperature was raised to 180°C for curing, and the curing and heat preservation time was 1 hour. Finally, the cured sample was placed in a high-temperature furnace at a heating rate of 5°C / min and heated to 800°C, and kept warm for 1 hour for carbonization to obtain a carbon fiber skeleton with a fiber volume fraction of 35%. The carbon fiber skeleton is placed in a shaped crucible with an inner surface coated with a release agent and the same dimensions as the outer dimensions of the fiber preform, a positive tolerance margin of 0.5 mm is reserved around the crucible, and a 0.5 mm graphite strip is placed on the bottom of the crucible to support the carbon fiber skeleton. The mass of the intermediate phase asphalt required for impregnation is calculated according to the porosity of the carbon fiber skeleton after the above-mentioned shaping, and the intermediate phase asphalt powder containing 10% of the required weight of the surplus is weighed and spread on the carbon fiber skeleton, and the crucible is placed in a cracking furnace; after the cracking furnace is evacuated, the vacuum state is maintained, and the temperature is raised to 110°C at a rate of 5°C / min. After keeping warm for 3 hours, nitrogen is introduced into the furnace, and the temperature is continued to rise to 400°C, and the temperature is kept warm for 7 hours to complete the asphalt impregnation. After the intermediate phase is converted, the temperature is finally raised to 900°C, the asphalt carbonization temperature, and kept warm for 1 hour to obtain a carbon skeleton modified with a first asphalt carbon matrix; the carbon skeleton is graphitized at 3000°C to obtain a C / C intermediate with high thermal conductivity; the same melt impregnation process is used to melt impregnate polycarbosilane with a ceramic yield of 50wt%, and in-situ cracking is performed. The melting point of polycarbosilane is 220°C. After melting and keeping warm for 5 hours, inert gas argon is introduced into the furnace, and the temperature is continued to be raised to 1200°C at a rate of 5°C / min. The temperature is kept warm for 1 hour to crack the polycarbosilane into a silicon carbide matrix; the polycarbosilane melt impregnation and in-situ cracking process are repeated 10 times to obtain a C / SiC composite material modified with an intermediate phase asphalt carbon matrix; like Figure 2 As shown in the scanning electron microscope image of the mesophase pitch carbon matrix modified high thermal conductivity C / SiC composite material prepared in Example 1, the prepared mesophase pitch carbon matrix modified high thermal conductivity C / SiC composite material has a bending strength of 202.38 MPa and an in-plane thermal conductivity of 124.15 W / (m·K).
[0016] Embodiment 2: A method for preparing a mesophase pitch carbon matrix modified high thermal conductivity C / SiC composite material comprises the following steps: The 2D twill stitched mesophase asphalt carbon fiber preform with T700 carbon fiber as stitching thread and stitched with 6mm / needle pitch was placed under vacuum conditions, immersed in 30% phenolic resin ethanol solution for 6 hours, dried in a 60℃ oven for 4 hours, and then heated to 110℃ in a hot molding device and pressurized at a pressure of 5MPa. After holding the pressure for 1 hour, the temperature was raised to 180℃ for curing. The curing and heat preservation time was 1 hour. Finally, the cured sample was placed in a high-temperature furnace with a heating rate of 5 ℃ / min to 900℃, keep warm for 1h for carbonization, and obtain a carbon fiber skeleton with a fiber volume fraction of 55%; place the above carbon fiber skeleton in a shaped crucible with an inner surface coated with a release agent and the same outer dimensions as the above fiber preform, reserve a positive tolerance margin of 0.5mm around the crucible, and place a 0.5mm graphite strip on the bottom of the crucible to support the carbon fiber skeleton. Calculate the mass of the intermediate phase asphalt required for impregnation according to the porosity of the carbon fiber skeleton after shaping in S1, and weigh the 15% residual The intermediate phase asphalt powder with a carbon yield of 55% is spread on the carbon fiber skeleton, and the crucible is placed in the cracking furnace; after the cracking furnace is evacuated, the vacuum state is maintained, and the temperature is raised to 110°C at a rate of 5°C / min. After keeping the temperature for 3 hours, nitrogen is introduced into the furnace, and the temperature is continued to rise to 400°C. After keeping the temperature for 7 hours to complete the intermediate phase conversion of the asphalt, the temperature is finally raised to 900°C, the asphalt carbonization temperature, and kept for 1 hour to obtain a carbon skeleton modified with a primary intermediate phase asphalt carbon matrix; the carbon skeleton is subjected to 3000°C stone Inking to obtain a high thermal conductivity C / C intermediate; the same melt impregnation process is used to melt impregnate polycarbosilane with a ceramic yield of 50wt%, and in-situ cracking, the melting point of polycarbosilane is 220℃, after melting and heat preservation for 5h, inert gas argon is introduced into the furnace, and the temperature is continued to rise to 1300℃ at a rate of 5℃ / min, and the temperature is kept for 2h to crack the polycarbosilane into a silicon carbide matrix; the polycarbosilane melt impregnation and in-situ cracking process is repeated 8 times to obtain a C / SiC composite material modified with an intermediate phase pitch carbon matrix; The prepared mesophase pitch carbon matrix modified high thermal conductivity C / SiC composite material has a bending strength of 196.76 MPa and an in-plane thermal conductivity of 264.01 W / (m·K).
[0017] Embodiment 3: A method for preparing a mesophase pitch carbon matrix modified high thermal conductivity C / SiC composite material comprises the following steps: The 2D twill stitched mesophase asphalt carbon fiber preform with M40J carbon fiber as stitching line and stitched with 5mm / needle pitch was placed under vacuum conditions, immersed in 20% phenolic resin ethanol solution for 6 hours, dried under infrared lamp for 8 hours, and then heated to 110°C in a hot molding device and pressurized at a pressure of 5MPa. After holding the pressure for 1 hour, the temperature was raised to 180°C for curing, and the curing and heat preservation time was 1 hour. Finally, the cured sample was placed in a high-temperature furnace with a heating rate of 5°C / min and heated to 800°C and kept for 1 hour for carbonization to obtain a carbon fiber skeleton with a fiber volume fraction of 35%. The carbon fiber skeleton is placed in a shaped crucible with an inner surface coated with a release agent and the same dimensions as the outer dimensions of the fiber preform, a positive tolerance margin of 0.5 mm is reserved around the crucible, and a 0.5 mm graphite strip is placed on the bottom of the crucible to support the carbon fiber skeleton. The mass of the intermediate phase asphalt required for impregnation is calculated according to the porosity of the carbon fiber skeleton after shaping, and the intermediate phase asphalt powder with a carbon yield of 55% and the required weight containing 10% of the remainder is weighed and spread on the carbon fiber skeleton, and the crucible is placed in a cracking furnace; after the cracking furnace is evacuated, the vacuum state is maintained, and the temperature is raised to 110°C at a rate of 5°C / min. After keeping warm for 3 hours, nitrogen is introduced into the furnace, and the temperature is continued to rise to 400°C. After keeping warm for 7 hours to complete the intermediate phase conversion of the asphalt, the temperature is finally raised to asphalt. The carbonization temperature is 900°C and kept for 1 hour to obtain a carbon skeleton containing part of the asphalt carbon matrix; the above asphalt melt impregnation + carbonization process is repeated once to obtain a carbon skeleton modified with a secondary intermediate phase asphalt carbon matrix; the carbon skeleton is graphitized at 3000°C to obtain a C / C intermediate with high thermal conductivity; the same melt impregnation process is used to melt impregnate and in-situ crack polycarbosilane with a ceramic yield of 50wt%, the melting point of polycarbosilane is 210°C, and after melting and heat preservation for 5 hours, inert gas argon is introduced into the furnace, and the temperature is continued to be raised to 1000°C at a rate of 5°C / min, and kept for 3 hours to crack polycarbosilane into a silicon carbide matrix; the polycarbosilane melt impregnation and in-situ cracking process are repeated 7 times to obtain a C / SiC composite material modified with an intermediate phase asphalt carbon matrix; like Figure 3 As shown in the scanning electron microscope image of the mesophase pitch carbon matrix modified high thermal conductivity C / SiC composite material prepared in Example 3, the prepared mesophase pitch carbon matrix modified high thermal conductivity C / SiC composite material has a bending strength of 191.93 MPa and an in-plane thermal conductivity of 160.75 W / (m·K).
[0018] Embodiment 4: A method for preparing a mesophase pitch carbon matrix modified high thermal conductivity C / SiC composite material comprises the following steps: A three-dimensional fine-woven puncture structure mesophase asphalt carbon fiber preform with a puncture needle pitch of 2mm / needle pitch was placed under vacuum conditions, immersed in a 20% phenolic resin ethanol solution for 6 hours, dried under an infrared lamp for 8 hours, and then heated to 110°C in a hot molding device and pressurized at a pressure of 5MPa. After holding the pressure for 1 hour, the temperature was raised to 180°C for curing, and the curing and heat preservation time was 1 hour. Finally, the cured sample was placed in a high-temperature furnace at a controlled heating rate of 5°C / min to 800°C and kept warm for 1 hour for carbonization to obtain a carbon fiber skeleton with a fiber volume fraction of 45%; The carbon fiber skeleton is placed in a shaped crucible with an inner surface coated with a release agent and the same dimensions as the outer dimensions of the fiber preform, a positive tolerance margin of 0.5 mm is reserved around the crucible, and a 0.5 mm graphite strip is placed on the bottom of the crucible to support the carbon fiber skeleton. The mass of the intermediate phase asphalt required for impregnation is calculated according to the porosity of the carbon fiber skeleton after shaping, and the intermediate phase asphalt powder with a carbon yield of 55% and a required weight containing 10% of the surplus is weighed and spread on the carbon fiber skeleton, and the crucible is placed in a cracking furnace; after the cracking furnace is evacuated, the vacuum state is maintained, and the temperature is raised to 110°C at a rate of 5°C / min. After keeping warm for 3 hours, nitrogen is introduced into the furnace, and the temperature is continued to rise to 400°C. After keeping warm for 7 hours to complete the intermediate phase conversion of the asphalt, the temperature is finally raised to the asphalt carbonization temperature. The mixture was kept at 900°C for 1 hour to obtain a carbon skeleton containing part of the asphalt carbon matrix; the asphalt melt impregnation + carbonization process was repeated once to obtain a carbon skeleton modified with a secondary intermediate phase asphalt carbon matrix; the carbon skeleton was graphitized at 2800°C to obtain a C / C intermediate with high thermal conductivity; the same melt impregnation process was used to melt impregnate and in-situ crack polycarbosilane with a ceramic yield of 50wt%, the melting point of polycarbosilane was 200°C, and after melting and heat preservation for 5 hours, inert gas argon was introduced into the furnace, and the temperature was continued to be raised to 1200°C at a rate of 5°C / min, and the temperature was kept for 1 hour to crack the polycarbosilane into a silicon carbide matrix; the polycarbosilane melt impregnation and in-situ cracking process were repeated 7 times to complete the densification of the composite material, and a C / SiC composite material modified with an intermediate phase asphalt carbon matrix was obtained; The prepared mesophase pitch carbon matrix modified high thermal conductivity C / SiC composite material has a bending strength of 220.89 MPa and an in-plane thermal conductivity of 140.82 W / (m·K).
[0019] Embodiment 5: The other process parameters and process of Example 5 are the same as those of Example 2, the main difference being that the mesophase pitch carbon modification was performed 4 times, and in the subsequent silicon carbide matrix preparation process, the polycarbosilane melt impregnation and in-situ cracking process were repeated 6 times to obtain a mesophase pitch carbon matrix modified C / SiC composite material; The prepared mesophase pitch carbon matrix modified high thermal conductivity C / SiC composite material has a bending strength of 176.31 MPa and an in-plane thermal conductivity of 288.22 W / (m·K).
[0020] Comparative Example 1: The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 does not perform the asphalt melt impregnation-carbonization process, that is, there is no mesophase asphalt carbon matrix modification, and the other process is the same as Example 1; The prepared C / SiC composite material has a flexural strength of 216.39 MPa and an in-plane thermal conductivity of 94.36 W / (m·K).
[0021] Comparative Example 2: The difference between Comparative Example 2 and Example 1 is that the fiber used in the fiber preform is PAN-based T300 fiber; The prepared C / SiC composite material has a flexural strength of 280.21 MPa and an in-plane thermal conductivity of 12.66 W / (m·K).
[0022] Comparative Example 3: The difference between Comparative Example 3 and Example 1 is that the subsequent densification process uses polycarbosilane solution impregnation instead of polycarbosilane melt impregnation, and the subsequent densification cycle requires 16 cycles; The density of the prepared C / SiC composite material: the flexural strength is 208.22MPa, and the in-plane thermal conductivity is 121.27W / (m·K).
[0023] Implementation effect analysis: Table 1 Properties of C / SiC composite materials prepared in various embodiments and comparative examples
[0024] It can be seen from the results obtained from the embodiments of the present invention and the comparative examples that: 1. The main difference between Example 1 and Example 2 is the difference in the volume fraction of the intermediate phase asphalt carbon fiber. It can be seen that with the increase in the volume fraction of the high thermal conductivity fiber, the thermal conductivity of the material increases, but an excessive increase in the fiber volume fraction will cause serious damage to the fiber in the S1 step, resulting in a certain degree of reduction in the bending strength of the material.
[0025] 2. Compared with Example 1, the main difference between Implementation 3 is that the mesophase asphalt carbon matrix modification was carried out once and twice respectively; compared with Example 2 and Example 5, the main difference is that the mesophase asphalt carbon matrix modification was carried out twice and four times respectively. Comparison of the results of these two groups of examples shows that the increase in the modification of the mesophase asphalt carbon matrix and the number of modifications can effectively increase the content of the mesophase asphalt carbon matrix in the composite material, and accordingly can effectively improve the thermal conductivity of the composite material.
[0026] 3. Although the fiber preform structures used in Example 4 and Example 3 are different, the main difference in the preparation process is that the graphitization temperature is reduced from 3000°C in Example 3 to 2800°C in Example 4. The graphitization treatment temperature has a great influence on the thermal conductivity of the material. The higher the graphitization temperature, the higher the degree of graphitization of the carbon fiber and the intermediate phase asphalt carbon, and the higher the thermal conductivity of the corresponding composite material.
[0027] 4. The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 does not perform asphalt melt impregnation and carbonization processes, that is, there is no mesophase asphalt carbon matrix modification, and other process steps are the same as Example 1. It can be seen that mesophase asphalt carbon matrix modification can effectively improve the thermal conductivity of the composite material.
[0028] 5. The difference between Comparative Example 2 and Example 1 is that the fiber used in the fiber preform is T300 carbon fiber with low thermal conductivity. It can be seen that the use of high thermal conductivity mesophase pitch fiber in the present invention can effectively improve the thermal conductivity of the composite material.
[0029] 6. The difference between Comparative Example 3 and Example 1 is that the subsequent densification process uses polycarbosilane solution impregnation instead of polycarbosilane melt impregnation. The performance of the composite material is equivalent, but the subsequent densification cycle requires 16 cycles. It can be seen that in the present invention, melt impregnation is used instead of solution impregnation, which can greatly shorten the process cycle and reduce the process cost.
[0030] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing a mesophase pitch carbon matrix modified high thermal conductivity C / SiC composite material, characterized in that: The following steps are involved: S1. Fiber preform shaping treatment: The fiber preform is placed under vacuum conditions, impregnated with phenolic resin solution, and then dried in an infrared lamp or a 60°C oven. It is heated to the softening temperature of phenolic resin in a hot molding device and then pressurized. The temperature is then raised to the phenolic resin curing temperature and the heat and pressure are maintained. Finally, the cured sample is carbonized in a high-temperature furnace to obtain a carbon fiber skeleton with a fiber volume fraction of 35% to 55%. The solvent of the phenolic resin solution is anhydrous ethanol, the mass fraction of the phenolic resin is 10% to 30%, the phenolic vacuum impregnation time is 4h to 8h, the drying time is 6h to 8h, the phenolic softening temperature is 90°C to 110°C, the pressure during softening is 1MPa to 5MPa, the holding time is 1h to 3h, the curing temperature is 180°C to 200°C, the curing holding time is 1 to 2h; the carbonization temperature is 800°C to 1000°C, the holding time is 1h to 3h, and the carbonization heating rate is 5°C / min to 10°C / min; The fiber preform is a 2D stitched mesophase asphalt carbon fiber preform or a three-dimensional fine-woven puncture structure mesophase asphalt carbon fiber preform, wherein the mesophase asphalt carbon fiber is a fiber that has not been graphitized; the carbon fiber cloth used for the 2D stitched preform is a satin or twill mesophase asphalt carbon fiber cloth, and the stitching spacing is 3mm / needle to 6mm / needle; the puncture needle spacing of the three-dimensional fine-woven puncture structure carbon fiber preform is 2mm / needle to 4mm / needle; the 2D stitched preform, stitched fiber and three-dimensional fine-woven puncture structure carbon fiber are selected from T300, T700, T800, M40J polyacrylonitrile-based carbon fiber; S2. Preparation of mesophase pitch carbon matrix: using a pyrolysis furnace to achieve melt impregnation of mesophase impregnated pitch, in-situ mesophase conversion of pitch and in-situ carbonization to obtain a mesophase pitch carbon matrix, specifically comprising the following steps: S2-1, placing the carbon fiber skeleton obtained in S1 in a shaped crucible with the inner surface of the inner surface coated with a release agent and the same outer dimensions as the carbon fiber skeleton, leaving a positive tolerance margin of 0.5 mm around the crucible, and padding the bottom of the crucible with a 0.5 mm graphite strip to support the carbon fiber skeleton, calculating the mass of the mesophase asphalt required for impregnation according to the porosity of the carbon fiber skeleton after shaping in S1, weighing the mesophase asphalt powder for impregnation containing the required weight of 10% to 15% of the surplus, and spreading it flat on the carbon fiber skeleton, and placing the crucible in a cracking furnace; S2-2, after the cracking furnace is evacuated, the vacuum state is maintained, and the temperature is raised to the melting point of the mesophase pitch at a rate of 5°C / min, so that the molten pitch is impregnated into the carbon fiber skeleton through the pores; S2-3, after the impregnation is completed, inert gas argon or nitrogen is introduced into the furnace, and the temperature is continued to be raised to the asphalt mesophase transformation temperature, and the temperature is maintained until the asphalt mesophase transformation is completed; S2-4, finally continue to raise the temperature to the pitch carbonization temperature to obtain a carbon skeleton modified with a primary mesophase pitch carbon matrix; The carbon yield of the mesophase pitch for impregnation is 45-55wt%; the heating rate of the pitch melting, mesophase conversion and carbonization process is 5°C / min, the melting point of the pitch is 90°C-110°C, the insulation time during melting is 3h-5h, the mesophase conversion temperature is 380°C-400°C, the insulation time is 7h-10h, the carbonization temperature is 900°C-1000°C, the insulation time is 1h-3h; S3, repeating the mesophase pitch melt impregnation, in-situ mesophase conversion, and in-situ carbonization process in S2 0 to 4 times to obtain a carbon skeleton containing 1 to 4 times of pitch carbon matrix modification; S4, graphitization treatment: the carbon skeleton modified by the asphalt carbon matrix obtained in S3 is placed in a graphitization furnace for high-temperature treatment, the graphitization temperature is 2800℃~3200℃; the heat preservation time is 1h~3h. During the graphitization treatment, the mesophase asphalt carbon fiber and the mesophase asphalt carbon matrix introduced in S2 and S3 are graphitized, and the thermal conductivity of the mesophase asphalt carbon fiber and the mesophase asphalt carbon matrix is stimulated; S5. Preparation of silicon carbide matrix: using the process in S2 to perform solid polycarbosilane melt impregnation and in-situ cracking: The graphitized carbon skeleton containing mesophase pitch carbon modification in S4 is placed in a contoured crucible coated with a release agent, and a 0.5 mm graphite strip is placed on the bottom of the crucible to support the carbon skeleton. The mass of solid polycarbosilane required for impregnation is calculated according to the porosity of the carbon skeleton in S4, and solid polycarbosilane powder containing 10% to 15% of the required weight of the residual is weighed on the carbon skeleton containing mesophase pitch carbon modification, and the crucible is placed in a cracking furnace; After the cracking furnace is evacuated, the vacuum state is maintained, and the temperature is raised to the melting point of polycarbosilane at a rate of 5°C / min, and the temperature is kept for 4h to 5h, so that the molten polycarbosilane is impregnated into the sample through the capillaries. After the impregnation is completed, an inert gas argon or nitrogen is introduced into the furnace, and the temperature is continued to be raised to 1000°C to 1300°C at a rate of 5°C / min, and the temperature is kept for 1h to 3h to crack the polycarbosilane into a silicon carbide matrix; The melting point of the polycarbosilane used for impregnation is 190°C to 220°C, and the ceramic yield is 50wt%; S6, repeating the polycarbosilane melt impregnation and in-situ cracking process in S5 for 6 to 10 times to complete the densification of the composite material to obtain a mesophase pitch carbon matrix modified high thermal conductivity C / SiC composite material; The prepared mesophase pitch carbon matrix modified high thermal conductivity C / SiC composite material has excellent mechanical and high thermal conductivity properties, with a flexural strength of 176.31MPa-220.89MPa and a thermal conductivity of 124.15W / (m·K)-288.22W / (m·K).
2. A mesophase pitch carbon matrix modified high thermal conductivity C / SiC composite material, characterized in that: The present invention also relates to a mesophase asphalt carbon matrix modified high thermal conductivity C / SiC composite material, which is obtained by the preparation method of the above-mentioned mesophase asphalt carbon matrix modified high thermal conductivity C / SiC composite material. The composite material has excellent mechanical and high thermal conductivity properties, a bending strength of 176.31MPa-220.89MPa, and a thermal conductivity of 124.15W / (m·K)-288.22W / (m·K).
Citation Information
Cited By
Ceramic and carbonaceous reinforced carbon-based composite bipolar plate material as well as preparation method and application thereof
CN119899042A
Porous SiC matrix, SiC / Al composite material and preparation method and application of SiC / Al composite material
CN121895070A